ТҮРКІ ТІЛДЕРІНДЕГІ СІЛТЕУ ЕСІМДІКТЕРІНІҢ ҚАЛЫПТАСУ ТАРИХЫ - Назарова, А. Ж. (Journal of Oriental Studies, 2016)
To determine to compare the word consistence and thehistory of pronouns of Turkish group language.